KONDISI, KEANEKARGAMAN DAN BENTUK PERTUMBUHAN KARANG DI PULAU KAYU ANGIN GENTENG, KEPULAUAN SERIBU - Wijaya, Citra Kusuma; Komala, Ratna; Giyanto, Giyanto (LPPM Universitas Negeri Jakarta, 2017)
Research on coral reefs in Pulau Kayu Angin Genteng, Kepulauan Seribu, which was conducted several years ago, obtained the condition of coral reefs and the diversity was medium. Therefore, this study aims to determine the condition of coral reefs, diversity, and the composition of the latest corals that exist in the Kayu Angin Genteng Island. This research was conducted in February - March 2017. The method used descriptive and data retrieval technique with Underwater Photo Transect (UPT). The number of stations consists of 4 locations based on the direction of the wind (North, East, South and West). Each station made of 30 m long transects placed at 2, 4, 6, 8 and 10 m depth. In addition, environmental parameters measurements include temperature, dissolved oxygen (DO), salinity, pH, light penetration and current velocity. Analysis of photo data using CPCe application. The results indicated that the condition of coral reefs in Kayu Angin Genteng Island belongs to enough category and the condition of water quality still supports coral life. The diversity index is included in the medium category. There are 11 growth forms, 17 family and 48 coral genus, based on the highest growth form composition represented by Acropora.